2011
DOI: 10.1111/j.1365-2591.2011.01881.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ropivacaine and articaine with epinephrine for infiltration anaesthesia in dentistry - a randomized study

Abstract: Ropivacaine (0.5%) achieved effective and long duration of uninflamed pulp and soft tissue anaesthesia. Ropivacaine could be useful for long-lasting operative procedures without the need for a vasoconstrictor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
1
11
0
5
Order By: Relevance
“…Complete anesthesia with articaine lasts for approximately 1 hour for infiltrations and up to approximately 2 hours for nerve block. [1112] Surprisingly, it has been observed that patients receiving 4% articaine with 1:100,000 epinephrine, had a significantly earlier onset of anesthetic effect as compared to 4% plain articaine (7.2 minutes vs. 9.2 minutes; P =.001) Even the duration of soft tissue anesthesia has been observed to be significantly longer in patients receiving 4% articaine with epinephrine as compared to 4% plain articaine (3.8 hours vs. 2.5 hours; P <.0001). [13]…”
Section: Pharmacologymentioning
confidence: 99%
“…Complete anesthesia with articaine lasts for approximately 1 hour for infiltrations and up to approximately 2 hours for nerve block. [1112] Surprisingly, it has been observed that patients receiving 4% articaine with 1:100,000 epinephrine, had a significantly earlier onset of anesthetic effect as compared to 4% plain articaine (7.2 minutes vs. 9.2 minutes; P =.001) Even the duration of soft tissue anesthesia has been observed to be significantly longer in patients receiving 4% articaine with epinephrine as compared to 4% plain articaine (3.8 hours vs. 2.5 hours; P <.0001). [13]…”
Section: Pharmacologymentioning
confidence: 99%
“…The existing information mainly refers to local anesthetic parameters obtained in volunteers [16][17][18][19][20], and limited data are available concerning the use of ropivacaine in dental practice [21][22][23]. There is a small note on the successful use of ropivacaine in a few oral surgical interventions, including extraction of impacted teeth [21,22,24], without mentioning the postoperative analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…Pesquisa prévia 17 comparou a eficácia, a latência e a duração da ação da ropivacaína 0,5% em relação à articaína 4% com epinefrina 1: 100 000 em um universo de 60 vonluntários, que foram submetidos à anestesia infiltrativa em região ântero-superior. Constatou-se, por meio do "pulp tester", que o tempo de latência foi significativamente menor para a ropivacaína quando comparado com articaína, assim como também a duração de ação e anestesia dos tecidos moles foram significativamente maior para a ropivacaína quando comparado à articaína.…”
unclassified
“…A articaína 4% com epinefrina 1:100.000 não apresentou diferenças significativas no tempo de latência, quando comparada à lidocaína 2%, associada à epinefrina 1:100.000 e a ropivacaína 7,5 mg/mL. Diferentemente dos achados literários, em que a articaína 4% com epinefrina 1:100.000 apresentou o tempo de latência superior ao da ropivacaína 17 e inferior ao da lidocaína 18 . Em um estudo 19 , de forma semelhante a este, avaliaram-se o tempo de latência e a duração anestésica da articaína a 4% com epinefrina 1:100.000, comparando-a à lidocaína a 2% com epinefrina 1:100.000, em bloqueios anestésicos do nervo alveolar inferior e anestesia infiltrativas do nervo bucal, em um universo de 30 voluntários.…”
unclassified
See 1 more Smart Citation